The Impact of Smart Contracts and Decentralized Finance Platforms on Transaction Costs in Indonesia's Traditional Economy - Judijanto, Loso; Anwar, Zainul; Budi, Hasiun; Sudarmanto, Eko; Sutanto, Himawan (Eastasouth Institute, 2024)
This study examines the impact of smart contracts and decentralized finance (DeFi) platforms on transaction costs within Indonesia's traditional economy. Using a quantitative approach, the research involved 60 respondents engaged in traditional economic sectors, utilizing a Likert scale (1-5) to gather perceptions on the efficiency, transparency, and cost-reduction potential of these technologies. Data were analyzed using SPSS version 25, with results indicating that both smart contracts and DeFi platforms significantly reduce transaction costs. Smart contracts were found to automate agreements and enhance trust, while DeFi platforms increased accessibility and reduced financial barriers. Regression analysis revealed that these technologies collectively explain 62% of the variance in transaction costs. The findings underscore the transformative potential of blockchain technologies in Indonesia's traditional economy, offering practical implications for stakeholders and policymakers to address technological and regulatory challenges. This research provides valuable insights for the integration of blockchain solutions in fostering economic efficiency and sustainability.